Genetic merit evaluation of second-generation Nile tilapia (GIFT) - Damas-Pérez, Teresa de Jesus; Barrueta-López, Daylen Virgen (Tropical Aquaculture, 2024)
The present study aimed to determine the genetic value of Nile tilapia GIFT in its second generation. The data evaluated corresponded to 19 families obtained from the genetic improvement program of tilapia in Cuba. An evaluation was performed on the entire population to determine each individual's genetic value, classifying it into high, medium, and low. The results obtained for high genetic merit were 362 and 322 grams for males and females, respectively, demonstrating the superiority of males over females for the live weight characteristic. The genetic parameters and variance components were estimated: additive, residual and phenotypic variance. As a fundamental element, heritability was estimated, characterized by being classified as high by obtaining a value of 0.49. The evaluation of genetic merit in genetic improvement programs represents a high potential to improve productivity through genetic selection.